A Multi Secret Sharing Approach for Vulnerability Identification in Social Media - Saman Mirza Abdullah (QALAAI ZANIST JOURNAL, 2021)
Online Social Networks (OSN)s become a suitable channel for attackers and threats to break system’s security and disclose privacies. In the few years, the demand on keeping OSN users safe from attackers was the trend of researchers. However, it was not a challenge-less process. The most significant challenge was the awareness of the OSN users about their vulnerability level. Works have been achieved to identify relations between OSN user vulnerability and the policies that used by attackers to penetrate systems, and then providing solutions, which were in the form of awareness that difficult for OSN users understand them. Different techniques, such as statistical and datamining tools, have been provided utilized to provide solutions for identifying vulnerabilities, however, target formation was still in primitive stages. This work presents a secrete sharing approach for computing the vulnerability percent of OSN users. The approach computes the rate of the vulnerability of an OSN user based on a polynomial equation.